Riachuelo nos jornais sergipanos (1860 - 1930) - Franco, Breno Assis Albuquerque (2023)
In the second half of the 19th century, on massapê soil, in the Cotinguiba Valley region, a settlement was born linked to the town of Laranjeiras, which in a period of less than fifteen years was promoted to parish, town and city. This urban development was monitored through narratives contained in newspaper publications in Sergipe, seeking from these documents to identify the dynamics that affected its socioeconomic development. However, the urbanization process cannot be understood as a successful endeavor, throughout its development, Riachuelo was a human cluster of somewhat affluent people, vulnerable to various diseases and natural disasters. Therefore, the work establishes a temporal limit between 1860, the decade indicated by the emergence of the human cluster, established by the construction of a chapel dedicated to Our Lady of Conceição, until the first 30 years of the 20th century, these marked by the organization of a policy dominated by the owners of land and sugar producers, mechanization in the processing of sugar cane, as well as a period of construction of structures that reaffirmed the distance from a rural setting to the city - market, meat butcher, East Brazilian railway installation, fabric factory , among others. Therefore, initially, this work is dedicated to tracing the heritage shared by the city and its agricultural enterprises. Followed by the understanding of economic and industrial diversification as mechanisms for transforming the city, based on the exploitation of labor, now organized no longer in mills, but rather in an urban nucleus. And finally, it is understood that the urbanization process is overcome when a political-administrative structure is foreseen, as well as means that enable the concentration of commercial activities, services and leisure.